Features of management of the general meeting in the creation of business society: international and dimensions - Polovynkina, Ruslana; Pavliuk, Tetiana; Sydorov, Yaroslav; Davydenko, Oksana (Management and Entrepreneurship: Trends of Development, 2025)
The article is devoted to the formation of new scientific decisions on the separation of features of management of the general meeting in the creation of a business society. Economic deregulation has not been found to solve the problems of effective and quality management of the authorized capital and corporate rights. Analysis of innovations of activity of governing bodies of companies was carried out. A list of issues to be resolved before the first meeting of the General Meeting is proposed. The practical implementation of the management of the general meeting in the creation of a company. The interconnection of the elements of effective management of the first meeting of the general meeting of participants in the creation of a business company is established. The procedure for registration and creation of legal entities in the United Kingdom and France has been clarified. The article aims is to develop practical recommendations for management of creation of a legal entity, as well as identifying the features of the first meeting of the general meeting. Methodology: The complex of general scientific and specialized methods at theoretical and empirical levels, such as synergistic to better understand the various processes of management of general meetings of legal entities, was used; communicative approach to determine the interaction of legal entity participants; The method of systematization, grouping and logical generalization in the disclosure of the competence of the general meeting of legal entities at the first meeting, as well as for generalization and systematization of conclusions and proposals; Comparative helped in the study of international experience in the creation of legal entities. The article uses the methods of logical generalization and scientific abstraction to identify key issues of organizing a meeting of general meetings, methods of analysis and synthesis helped with the researched components of management, in a single interconnection of all elements. Results: Practical recommendations for the management of the creation of a legal entity, as well as identify the features of the first meeting of the general meeting were developed.JEL Classification: K19, K40